Fiscal federalism principles and practices of multiorder governance - Boadway, Robin W. 1943- (Cambridge University Press, 2009)
This book provides a comprehensive account of the principles and practices of fiscal federalism based on the currently accepted theoretical framework and best practices. The traditional topics of assignment of responsibilities, intergovernmental fiscal arrangements, fiscal competition, and grants are covered in a unified framework with reference to actual practices followed in federations around the world. Special issues such as local government and the implications of natural resource issues are considered along with emerging issues such as governance, corruption, and the effect of globalization and the information revolution on the nation state. The treatment is non-technical and suitable for a wide variety of audiences, including scholars, instructors, students, policy advisors, and practitioners
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Intergovernmental fiscal relations; Fiscal policy; Decentralization in government; Revenue sharing; Fiskalföderalismus